The Problem of Religious Tolerance in Indonesia from the Perspective of Human Rights Based on Law Number 39 of 1999 - Rexa Ridho Pradipta; Ika Ariani Kartini (Jurnal Indonesia Sosial Sains, 2026)
Indonesia, as a nation with high religious diversity, faces persistent challenges in guaranteeing freedom of religion, particularly regarding permits for constructing houses of worship. Although Article 22 of Law No. 39 of 1999 on Human Rights explicitly protects this fundamental right, the Joint Regulation of Two Ministers No. 9 and 8 of 2006 which requires user lists, community support, and recommendations from the Religious Harmony Forum (FKUB) has frequently become an instrument of bureaucratic discrimination against minority religious groups. Monitoring data from SETARA Institute and the National Commission on Human Rights record hundreds of cases of worship disruption, church sealing, and rejection of building permits between 2007 and 2023, indicating a persistent gap between constitutional norms and field practice. This study employed a normative juridical method with statute and literature approaches, analyzing legislation related to house of worship permits and their relation to human rights protection in Indonesia. The findings show that obstacles are not merely administrative but also stem from social resistance, narrow majority-minority interpretations, weak local policy implementation, and inconsistent law enforcement, which together constitute violations of the right to religious freedom, the right to security, and the right to protection from discrimination as guaranteed by Law No. 39/1999. Case patterns such as GKI Yasmin Bogor and various church disputes in Cilegon and Tanjung Balai Karimun reveal how community support requirements are often manipulated as a "veto tool." The study recommends reinterpreting or revising the Joint Ministerial Regulation, strengthening consistent human rights-based law enforcement, positioning FKUB as a neutral facilitator, and investing in tolerance education to bridge formal and substantive religious tolerance in Indonesia.